2009
DOI: 10.1182/blood-2008-11-189407
|View full text |Cite
|
Sign up to set email alerts
|

microRNA-29c and microRNA-223 down-regulation has in vivo significance in chronic lymphocytic leukemia and improves disease risk stratification

Abstract: Aberrant expression of microRNAs has been recently associated with chronic lymphocytic leukemia (CLL) outcome. Although disease evolution can be predicted by several prognostic factors, a better outcome individualization in a given patient is still of utmost interest. Here, we showed that miR-29c and miR-223 expression levels decreased significantly with progression from Binet stage A to C were significantly lower in poor prognostic subgroups (defined by several prognostic factors) and could significantly pred… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

19
129
1
4

Year Published

2009
2009
2020
2020

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 224 publications
(153 citation statements)
references
References 35 publications
19
129
1
4
Order By: Relevance
“…In addition, we showed that this release was not specific to miR-150: indeed, when an irrelevant CLL microRNA was electroporated (as miR-1, which is normally absent in CLL), it was also released in a higher proportion from cellular miR-150 low patients (data not shown). This result is consistent with the fact that low levels of other microRNAs such as miR-34a, mir-29 and miR-223 have been observed in patients with poor prognostic CLL (21,33).…”
Section: R E S E a R C H A R T I C L E M O L M Esupporting
confidence: 91%
See 1 more Smart Citation
“…In addition, we showed that this release was not specific to miR-150: indeed, when an irrelevant CLL microRNA was electroporated (as miR-1, which is normally absent in CLL), it was also released in a higher proportion from cellular miR-150 low patients (data not shown). This result is consistent with the fact that low levels of other microRNAs such as miR-34a, mir-29 and miR-223 have been observed in patients with poor prognostic CLL (21,33).…”
Section: R E S E a R C H A R T I C L E M O L M Esupporting
confidence: 91%
“…In addition, we showed that this release was not specific to miR-150: indeed, when an irrelevant CLL microRNA was electroporated (as miR-1, which is normally absent in CLL), it was also released in a higher proportion from cellular miR-150 low patients (data not shown). This result is consistent with the fact that low levels of other microRNAs such as miR-34a, mir-29 and miR-223 have been observed in patients with poor prognostic CLL (21,33).Extracellular microRNA could circulate in body fluids in different forms: encapsulated in microvesicles, in exosomes or associated with protein/lipid complexes. In the present study, by using different speeds of centrifugation, we demonstrated that a small part of miR-150 circulates within microvesicles, but that the majority of circulating miR-150 is most likely associated with protein/lipid complexes because free microRNA will be rapidly degraded by RNAse.…”
supporting
confidence: 88%
“…The fact that neither miR-29 nor miR-181 is located at 11q chromosomal region suggests that deletions in this region may affect an unknown regulator of the expression of these two microRNAs 6 . These results were confirmed by Stamatopoulos et al who showed that miR-29c negative patients expressed significantly higher levels of Tcl-1 compared with miR-29c positive patients 62 .…”
Section: Mir-29 As a Regulator Of Tcl-1supporting
confidence: 80%
“…Decrement of miR-223 is often observed in leukemia disease, 12 while increased expression of miR-223 is mainly seen in solid cancer types including HNSCC. 13,14 In the present study, we consistently found that miR-223 expression was enhanced in HNSCC cancerous tissues.…”
Section: Discussionmentioning
confidence: 99%